(untitled) (Revista de Psicología, 2018)
It is demonstrated that insane perfectionism arises at an early age and has important long-term clinical consequences. The objective of this work was to investigate what has been investigated about children’s perfectionism in Argentina, highlighting the instrumental and theoretical advances that have been made in this line during the last 15 years. Different databases were consulted and institutional and personal contacts were established to collect the available information. We identified 15 empirical studies on the subject, carried out with children between 8 and 13 years of age, from different provinces and regions of the Argentine Republic. The corpus of analysis included scientific articles published in national and international journals, undergraduate and graduate theses, and research projects. Argentine research has been able to reveal which variables in the family environment and which characteristics of the child itself play an important role In the development of maladaptive perfectionism, and have demonstrated how it impairs psychosocial adjustment during childhood, putting at risk physical, social and emotional well-being. In relation to the diagnostic area, two psychometric instruments with proven validity and reliability were registered, as well as reference values t o establish the perfectionist profile of Argentine children according to their age and gender.